Interwencjonizm i liberalizam a rozwój zrównoważony rolnictwa i obszarów wiejskich - Szydło, Wiktor (Interventionism and liberalism due to sustainable development of agriculture and rural areas, 2007)
The article discusses an influence of liberał and interventionist concepts on sustainable development of agriculture and rural areas. Solving problems of agriculture and rural areas by means of liberał concepts seems to be unfeasible. Interventionism is essential, yet its current shape should change. It is especially necessary to reduce the disproportion in the level of agricultural support among EU countries, shift morę funds for development of rural areas (for example at the expense of big farms) and take into account the needs of Third World countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 356-368